2021
DOI: 10.1007/s11695-021-05282-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Multivitamin Supplementation for Sleeve Gastrectomy Patients

Abstract: Purpose Micronutrient deficiencies are frequently reported after sleeve gastrectomy (SG), and therefore lifelong daily multivitamin supplementation is highly recommended. Based on literature and the results of a previous randomized controlled trial, a specialized multivitamin supplement for SG patients was further optimized (WLS Optimum 2.0, FitForMe). The present study reports on its short-term effectiveness. Materials and Methods An open-label study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(26 reference statements)
1
7
0
Order By: Relevance
“…Our findings are in line with other reports describing elevated plasma vitamin B6 levels in postbariatric patients upon regular multivitamin intake 16,[18][19][20][21][22][23][24] , challenging the assumption that the postbariatric status per se is associated with a risk for vitamin B6 deficiency. This is supported by the observation that postbariatric vitamin B6 deficiency was mainly reported in patient collectives where a deficiency was already present before surgery 13,25,26 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with other reports describing elevated plasma vitamin B6 levels in postbariatric patients upon regular multivitamin intake 16,[18][19][20][21][22][23][24] , challenging the assumption that the postbariatric status per se is associated with a risk for vitamin B6 deficiency. This is supported by the observation that postbariatric vitamin B6 deficiency was mainly reported in patient collectives where a deficiency was already present before surgery 13,25,26 .…”
Section: Discussionsupporting
confidence: 92%
“…While supplementation of various macro-and micronutrients is important to prevent deficiencies after bariatric surgery 30 and recommended by various society guidelines 15 , a substantial body of evidence points towards an over-supplementation of post-bariatric patients by daily vitamin B6 intake 16,[18][19][20][21][22][23][24]27,28 . Thus, prospective, multicenter studies are needed to unravel, if multivitamin formulations recommended to post-bariatric patients should be adapted regarding their vitamin B6 content to avoid over-supplementation and possible associated side effects in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Seventy-five percent of all participants reports taking MVS 12 years after surgery, and there is no difference between FA and IFA. Heusschen et al reported a compliance rate of 55% at 12 months even though the participants received the MVS for free the first year after surgery [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…reason, a specialized multivitamin supplement specifically targeted to the needs of SG patients was developed (WLS Optimum; FitForMe, Rotterdam, the Netherlands). The composition of WLS Optimum was previously evaluated in a randomized controlled trial and optimized afterwards [11,12]. The first version of WLS Optimum (1.0) was effective in reducing the prevalence of anemia and improving serum levels of folic acid, PTH, and vitamin B1 1 year after SG in comparison to a standard, over-the-counter multivitamin supplement (sMVS) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The first version of WLS Optimum (1.0) was effective in reducing the prevalence of anemia and improving serum levels of folic acid, PTH, and vitamin B1 1 year after SG in comparison to a standard, over-the-counter multivitamin supplement (sMVS) [11]. The optimized version of WLS Optimum (2.0) additionally improved serum levels of vitamin B12, vitamin B6, and zinc, and resulted in less deficiencies for vitamin B12 and phosphate during the first year after SG, in comparison to WLS Optimum 1.0 [12]. However, the effectiveness of such specialized MVS on the longer term after SG is still unknown.…”
Section: Introductionmentioning
confidence: 99%